Open Data Revolution in Clinical Research: Opportunities and Challenges - Mohamed H. Shahin; Sanchita Bhattacharya; Diego Silva; Sarah Kim; Jackson Burton; Jagdeep Podichetty; Klaus Romero; Daniela J. Conrado (Wiley, 2020)
Efforts for sharing individual clinical data are gaining momentum due to a heightened recognition that integrated data sets can catalyze biomedical discoveries and drug development. Among the benefits are the fact that data sharing can help generate and investigate new research hypothesis beyond those explored in the original study. Despite several accomplishments establishing public systems and guidance for data sharing in clinical trials, this practice is not the norm. Among the reasons are ethical challenges, such as privacy of individuals, data ownership, and control. This paper creates awareness of the potential benefits and challenges of sharing individual clinical data, how to overcome these challenges, and how as a clinical pharmacology community we can shape future directions in this field.